2015
DOI: 10.2141/jpsa.0150061
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between Morphological, Densitometric and Mechanical Properties of Eggs in Japanese Quails (<i>Coturnix Japonica</i>)

Abstract: Eggshell quality in birds results from mineral density and composition determining its mechanical endurance. The aim of the study was to determine interrelationships between morphological, densitometric and mechanical properties of eggs in Japanese quails. Twenty four eggs randomly collected from 17-week-old quails were subjected to morphological, denstiometric and mechanical evaluation using dual-energy X-ray absorptiometry (DEXA), quantitative computed tomography (QCT) and three-point bending test. Weight, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Hence, the eggshell thickness was significantly affected by laying hen genotypes in spite of the non-significant effect on eggshell strength. This finding might be explained by Tatara et al (2016) who indicated that the mechanical endurance of the eggshell is not simply affected by its thickness but by other factors, e.g. mineral density, mineral content, and spatial micro architectural arrangement contribute to this characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the eggshell thickness was significantly affected by laying hen genotypes in spite of the non-significant effect on eggshell strength. This finding might be explained by Tatara et al (2016) who indicated that the mechanical endurance of the eggshell is not simply affected by its thickness but by other factors, e.g. mineral density, mineral content, and spatial micro architectural arrangement contribute to this characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with Kibala et al (2015) who reported a positive genetic correlations between eggshell strength and its thickness. On the other hand, Tatara et al (2016) revealed a negative correlation between eggshell thickness and eggshell strength, indicating that mechanical endurance of the eggshell is not simply affected by its thickness but other factors such as mineral density, mineral content and spatial micro architectural arrangement contribute to this characteristic. Results of the present study indicated a significantly positive correlation between egg shape index and eggshell strength in both housing systems.…”
Section: Discussionmentioning
confidence: 96%
“…The authors observed a genetic correlation between eggshell strength and its thickness to be around 0.8, making shell thickness a selection index candidate element. Tatara et al (2016) used dual-energy X-ray absorptiometry, quantitative computed tomography, and three-point bending test and they found positive correlation between weight, height, and width of eggs and egg mineral content and egg volume. Moreover, the mean volumetric eggshell mineral density was positively correlated with eggshell breaking strength and negatively correlated with eggshell thickness.…”
Section: Eggshell Quality and Its Measurementsmentioning
confidence: 99%